Response of Broilers to Feeding Manipulations - Oyedeji, J.O.; Atteh, J.O. (International Journal of Poultry Science, 2005)
The study investigated the response of broilers to different feeding manipulations. Six groups of day old Anak broilers were randomly assigned to either one of the following feeding methods from day old to 3 weeks; Ad libitum feeding, Skip-a-day feeding, 50% of ad libitum feeding, 6 hours of light and 18 hours of darkness per day, 3% dietary ammonium sulphate or diet containing 18% protein and 2800 kcal/kg ME. Broilers were thereafter fed the same finisher diet to market age. Results at market age showed that feed intake was significantly reduced by all but one of the feed restriction methods investigated (P< 0.05, P0.05, P>0.01). Feed to gain ratio was significantly reduced in broilers placed on 50% of ad libitum feeding (P0.01). Cost to benefit ratio of broiler production was significantly reduced by skip-a-day and 50% of ad libitum feeding methods (P